Design of a pyrolysis system and the characterisation data of biochar produced from coconut shells, carambola pruning, and mango pruning using a low-temperature slow pyrolysis process - Mohammad Shahid Shahrun; Mohammad Hariz Abdul Rahman; Nur Adliza Baharom; Fauzi Jumat; Mohamad Jani Saad; Mohd Fazly Mail; Norziana Zin Zawawi; Farah Huda Sjafni Suherman (Data in Brief, 2024)
Biochar production is an effective approach to managing abundant agricultural wastes. Pruning wastes from trimming the branches of trees such as carambola and mango, as well as coconut shells, are among the agricultural wastes that have reutilisation potential, which would simultaneously reduce the space required for disposal. In this study, the potential use of these wastes by converting them into biochar was investigated. The data presented in this study highlight the design of a pyrolysis system for a low-temperature slow pyrolysis process, as well as the characterisation data of the biochar produced using this system. The data collected included the elemental composition, porosity, as well as surface and adsorption characteristics of the biochar. These data indicate that the biochar produced had certain qualities that would enable its use for specific agricultural and industrial purposes. Meanwhile, the design indicated that it could facilitate small farms with specific outputs. In brief, these data can be used as references for developing a small-scale system for agricultural waste management using different types of crops.